Cervical Cancer, Different Treatments and Importance of Bile Acids as Therapeutic Agents in This Disease - Šarenac, Tanja; Mikov, Momir (Frontiers in Pharmacology, 2019)
Cervical cancer can be cured, because it has a long preinvasive period. Early diagnosis and treatment of cervical cancer at women are crucial for reducing of rate mortality. Today, there are many methods for detecting premalignant lesions and one of them is a conventional Papanikolau test. Cervical cancer develops through a series of changes in the epithelium called cervical intraepithelial neoplasia (CIN). The biological and genetic characteristics of the cells at cancer in situ are irreversibly altered and abnormal cells have the potential to metastasize to others anatomical regions. Infection with human Papilomavirus, which is transmitted sexually, is considered the main cause and represent the necessary, but not the only factor for the development of cervical cancer. Types of high risk human Papilomavirus are often associated with invasive cervical cancer. The carcinogenic types of HPV 16 and 18 are responsible for 70% of cervical cancer and about 50% of cervical intraepithelial neoplasia, CIN 3. Primary prevention of cervical cancer is aimed at reducing incidence, control of causes and risk factors. In this scientific work, in addition to explaining the various treatments necessary for the treatment of cervical carcinoma, we were discussed about the anticancer effects of the synthetic derivative of ursodeoxycholic acid, such as HS−1183, and synthetic derivatives of chenodeoxycholic acid such as HS−1199 and HS−1200. Also, the effects of bile acid complexes with metals such as platinum, zinc, nickel and cooper were considered in the effective treatment of cervical cancer